Effect of Pioneer Aeromedical Evacuation Program on Flight Medics’ Knowledge toward Emergency Casualties at Army Aviation Bases in Iraq - Kadhum, Ammar; Baker, Huda (Iraqi National Journal of Nursing Specialties, 2020)
Objective(s): The aims of present study to findout the effect of aeromedical evacuation program on flight medics’ knowledge. Methods: A pre-experimental design is carried in army aviation bases in Iraq, for the period of April 1st 2019 to October 25th 2019. Non-probability "purposive" sample of (30) flight medics are selected from army aviation bases. The questionnaire consisted of two main parts: the demographic characteristics of air paramedics, and the second part included five axes, which are (50) paragraphs related to the knowledge of air paramedics towards emergency injuries. The researcher used the statistical program version 20 to analyze the data, and the stability of the questionnaire was measured through the pre and post testing, and the validity was determined The content of the tool through its presentation to expert experts, and the data was analyzed through the use of descriptive and deductive statistical analysis. Results: The results of the study indicated that the knowledge of paramedics related to the air evacuation of the five axes was moderate level in the pre-test and their knowledge was improved in the first and second post-test. The study revealed that there were relationship for the effectiveness of the program with the location of the training course for the paramedic participating in the study at P ≥0.05 level Recommendations: The study recommended the approval of the current program in the implementation of training courses related to emergency cases during aeromedical evacuation